Orchidaceae in the Parque Natural Municipal da Restinga de Praia do Forte, Bahia, Brazil - Fajardo Villela Antolin Barberena, Felipe; da Silva Sousa, Tainan; Roque, Nádia (Instituto de Ecología, A.C., 2023)
Background and Aims: Bahia is one of the Brazilian states with the greatest diversity of orchids. Species restricted to microhabitats or forming small populations, being subject to local suppression, have been reported for restingas of the state. The north coast of Bahia has recently been exposed to intense anthropic pressures, including disordered occupation of land and predatory tourism. In order to encourage the adoption of regional conservation strategies, we carried out a survey of the orchid flora in the Parque Natural Municipal da Restinga de Praia do Forte (PNMR Praia do Forte), a fragment of restinga on the north coast of the state. Methods: Field work was conducted monthly from September 2016 to December 2017, and in July 2020 and August 2022, by employing the walking survey method. We consulted collections of the herbaria ALCB, HRB, HUEFS, and RB in person, as well as digital images of type specimens deposited in European herbaria and the Environmental Information Reference Center database. Phenological and distribution data of the species in the phytophysiognomies of PNMR Praia do Forte were mostly obtained in the field. Key results: Orchidaceae is represented by 14 genera and 16 species in the PNMR Praia do Forte, most of which are native to the Neotropics (14 spp., including eight endemic to Brazil), mainly terrestrial (six spp.), occurring exclusively in restinga forest formations (eight spp.). Epistephium williamsii, Gomesa barbata, Oeceoclades maculata, Pachygenium parvum, Polystachya concreta and Prescottia leptostachya (restricted to Bahia state) form small populations (<50 individuals). Conclusions: The orchid flora of the PNMR Praia do Forte, especially the aforementioned species, requires the attention from managers, in order to implement possible management and conservation actions and prevent them from being suppressed locally. We suggest greater surveillance actions in the park and environmental education actions among local residents and tourists.